How much does an antiinflammatory treatment cost? - S. Adami; G. Colombo; O. Viapiana; D. Gatti (PAGEPress Publications, 2011)
NSAIDs are among the most popular drugs in the world for their efficacy in controlling pain and acute and chronic inflammation. The efficacy of these therapies is hampered by their safety profile, in particular regarding the gastroenteric tract. The NSAIDs' side effects may heavily influence the health of the single patient and the economy of the health systems. The pharmacoeconomic evaluation of antinflammatory treatment usually considers, in addition to the drug purchase prize, also the shadow costs. This cost is mainly due to the management and prevention of gastropathy. Coxibs, even if more expensive, may become cost-effective for their better gastronteric safety. As a matter of fact, coxib treatment can be considered equivalent to a treatment with NSAID plus PPI. However, the first requirement of these drugs, that should control pain, must be the efficacy and not only safety. In this case the NNT (Number Needed to Treat) is a good marker of efficacy. To calculate the real cost we must pay to reach the target (pain resolution in one patient), we can multiply NNT for the prize of a specific drug. The total cost will depend on drug prize (the cheaper, the better) and on the efficacy expressed by NNT (the lower, the better). In a recent meta-analysis, the NNT of several antinflammatory drugs has been calculated. When the treatment cost was adjusted for its efficacy (NNT), the difference in favour of NSAIDs became so little to disappear because of the higher safety of coxibs (especially of etoricoxiband the possibility to reach antinflammatory and analgesic doses that are difficult to obtain with NSAIDs. Moreover, if also the cost of gastroprotection is considered, the economic impact of NSAIDs can be much higher. In conclusion the pharmacoeconomic analysis of an antinflammatory therapy cannot be based only on safety issues but also on efficacy evaluation that is the main effect we ask to these drugs.